The Equal Parent Presumption: Social Justice in the Legal Determination of Parenting After Divorce - EDWARD KRUK (McGill-Queen's University Press, 2013)
The subject of this book has been a preoccupation of mine since 1985. At that time, I embarked on PhD research examining why so many fathers became disengaged from their childrenâ€™s lives after divorce. My conclusion was that a legal decree of shared parenting would be the most effective measure to prevent what was in effect legally sanctioned parental alienation after divorce. Since that time, childrenâ€™s relationships with their parents generally have continued to erode in Canada â€“ the result of misguided child and family policies â€“ much to the detriment of childrenâ€™s well-being and healthy development. Since that initial foray into divorce research, I have expanded my research focus to include mothers and children of divorce, divorce practitioners, and the impact of family law in the realm of contested child custody. The people who have assisted me in this lifetime effort are far too numerous to name, and I restrict myself to acknowledging those who have contributed to this bookâ€™s development in the recent past. First and foremost, thanks to legal scholar Natalie Nikolina of the Utrecht University School of Law, and to the entire international network of shared parenting scholars organized by Alexander Masardo at the University of Birmingham. Natalieâ€™s article, â€œThe Influence of International Law on the Issue of Co-Parenting,â€ was discussed by this group, and set the stage for the development of the first chapters of this book. I owe her a debt for her assistance in critiquing earlier drafts of this book, and for helping me to clarify key points. Her perspective as a scholar of international family law inspired me to set aside dominant discourses and antiquated thinking about child custody in favour of a new paradigm, that of co-parenting after divorce, which clarifies the meaning of â€œequal parenting.â€